Use of Plant Genetic Resources: Germplasm [Presentation] - Andrade, Robert Santiago; Gutiérrez, Daniel; Álvarez, Diego A.; Ocampo, John; Tohme, Joseph M.; González, Carolina (2022)
This presentation presents diverse examples of impact from the distribution of germplasm. It is based on the Policy Brief: Globetrotting crops: A contribution by ICA and the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT) to agricultural research (https://hdl.handle.net/10568/118369). It was presented during the Future Seed inaguration event